Obesity‐Associated Dysregulation of Calpastatin and MMP‐15 in Adipose‐Derived Stromal Cells Results in their Enhanced Invasion123. (27th November 2012) - Strong, Amy L.; Semon, Julie A.; Strong, Thomas A.; Santoke, Tatyana T.; Zhang, Shijia; McFerrin, Harris E.; Gimble, Jeffrey M.; Bunnell, Bruce A.
Abstract: Adipose tissue maintains a subpopulation of cells, referred to as adipose‐derived stromal/stem cells (ASCs), which have been associated with increased breast cancer tumorigenesis and metastasis. For ASCs to affect breast cancer cells, it is necessary to delineate how they mobilize and home to cancer cells, which requires mobilization and invasion through extracellular matrix barriers. In this study, ASCs were separated into four different categories based on the donor's obesity status and depot site of origin. ASCs isolated from the subcutaneous abdominal adipose tissue of obese patients (Ob + Ab + ) demonstrated increased invasion through Matrigel as well as a chick chorioallantoic membrane, a type I collagen‐rich extracellular matrix barrier. Detailed mRNA and protein analyses revealed that calpain‐4, calpastatin, and MMP‐15 were associated with increased invasion, and the silencing of each protease or protease inhibitor confirmed their role in ASC invasion. Thus, the data indicate that both the donor's obesity status and depot site of origin distinguishes the properties of subcutaneous‐derived ASCs with respect to enhanced invasion and this is associated with the dysregulation of calpain‐4, calpastatin, and MMP‐15. STEM CELLS 2012;30:2774–2783